Pelatihan Crochet Accessories Sebagai Peluang Usaha - Iqlima Nur Syabana; Afifah Devianda Prastiwi; Alifa Nur Azifa; Ika Prihandini; Aisha Karmelita Cinta (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The Community Service carried out by Semarang University students has the aim of helping the development of Micro, Small and Medium Enterprises in Central Java, especially in the City of Semarang. It is also hoped that this training will be able to provide services or create employment opportunities for participants who have taken part in crochet training with Pradita Rahmawati as a resource person who supports and teaches participants about the basics of knitting techniques as well as practicing knitting with ribbons as the object and final result of the training. The final results of this community service include several things including scientific publications, training modules, increasing participants' knowledge about crochet, interesting video profiles as well as the sustainability of knitting services in Indonesia and the progress of Micro, Small and Medium Enterprises.